The history of sturgeon in the Baltic Sea. (3rd April 2014) - Popović, Danijela; Panagiotopoulou, Hanna; Baca, Mateusz; Stefaniak, Krzysztof; Mackiewicz, Paweł; Makowiecki, Daniel; King, Tim L.; Gruchota, Jakub; Weglenski, Piotr; Stankovic, Anna; Parmakelis, Aristeidis
Abstract Aim Migrants of the Atlantic sturgeon, Acipenser oxyrinchus, from North America are thought to have founded the Baltic sturgeon population during the Little Ice Age around 1200 years ago, replacing the European sturgeon, Acipenser sturio. To test this hypothesis and to further elucidate the colonization of the Baltic Sea by A. oxyrinchus, we carried out DNA analyses of ancient and contemporary populations of both species. Location We analysed DNA from 188 specimens of sturgeons collected from archaeological sites and museums in Poland and of 225 contemporary specimens from North American and European populations. Methods Several mitochondrial DNA fragments were sequenced and eight microsatellite loci were genotyped for species identification, polymorphism and population structure analyses. Approximate Bayesian computation was used to estimate when the Baltic Sea was colonized. Results Of 125 ancient sturgeon specimens from the Baltic Sea, only four were classified as A. sturio, the remainder being A. oxyrinchus oxyrinchus. The ancient A. o. oxyrinchus population over two different time periods was highly polymorphic and genetically distant from contemporary populations of this taxon. The time of entry into the Baltic Sea was estimated to be 4000–5000 years ago. We also detected introgression of A. sturio into the A. o. oxyrinchus gene pool, caused by a prior hybridization event. Main conclusions For the past 2000 years at least, A. o. oxyrinchus has been the dominant sturgeon in the Baltic Sea, indicating a much earlier origin than previously suggested. The most similar extant sturgeon populations to the extinct Baltic stock are those from the St John and St Lawrence rivers in Canada. These populations should be considered the best source of breeding material for the ongoing sturgeon restitution programmes in Poland and Germany.